Appropriateness of the post-operative rehabilitation of low energy hip fractures in elderly in comparison with the AAOS appropriate use criteria at a level one trauma center - Mohammed Adam (14150655) (2022)
Purpose This study aimed to assess the appropriateness of the post-operative rehabilitation of low energy hip fractures in the elderly by comparing between the rehabilitations actually provided at level one trauma center and the AAOS Appropriate Use Criteria (AUC) recommendations. Methods A retrospective review of the medical charts of all patients who underwent surgery for hip fractures followed by post-operative rehabilitation between October 2016 and May 2018. The age, gender, fracture types, four AUC variables including; the surgical approach, pre-operative mobility/functional status, cognitive impairment, and post-operative delirium, and types of post-operative rehabilitation received were collected. The four patient variables were entered into the AUC application to generate the recommended rehabilitation procedures. Afterward, the rate of appropriateness of the treatments and the agreement between the rehabilitations actually provided and the AUC recommendation were measured. Results Over the study period, a consecutive series of 101 patients were included. The mean age was 75 years. Most of the patients were males (51.5%). Seventeen scenarios were observed in our patients. The most common scenario were patients with low functional/physical demands (48%), intact cognitive function (91%), non-arthroplasty approach (76%), and no post-operative delirium(97%). The overall appropriateness rate of the provided rehabilitation treatments for our patients in comparison with AUC recommendation was appropriate in 356 (48.7%) (P = .001), maybe appropriate in 19 (3%) (P < .001), rarely appropriate in 61 (8.3%) (P = .59), and 40% of rehabilitation procedures were not provided (P < .001). The actual treatment was appropriate and in agreement with the AUC recommendations in (100%) of three procedures (Deep venous thrombosis prophylaxis, pain management, and Inpatient Rehabilitation Facility or Skilled Nursing Facility), in (72.2%) of osteoporosis assessment/management, in (63.8%) of outpatient occupational/physical therapy, in (10.2%) of delirium prevention, in (33.3%) of delirium management and in (25%) of home care therapy. Conclusions This study demonstrated that there is a remarkable variation in the appropriateness of the various post-operative rehabilitation procedures for elderly hip fracture. Additionally, the AUC application was easy to use and simple for identifying post-operative rehabilitation protocols for elderly hip fractures, hence, we recommend to use it in the trauma clinical practice. Level of evidence: IV Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00590-021-02938-w